Inspection Process of Notary as Witnesses and Suspects in The Case of Crime - Adad Adad; Widayati Widayati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The existence of the Notary institution based on the needs of the community in making authentic act as a binding evidence. Notary role in serving the public interest is providing services in deed and other tasks that require the services of a Notary. Deed issued by Notary ensuring legal certainty for the public. Notaries have a role as well in running the legal profession can not be separated from the fundamental issues relating to the functions and role of the law itself. The authority Notary as stated in Article 15 UUJN is made the authentic act on all deeds, agreements, and provisions required by legislation and / or desired by an interested party, to be stated in an authentic deed, guaranteeing the creation date of the deed, saving certificates, provide a copy, and official copies, all along the deed is not assigned or excluded to officials or other persons specified by law. Notaries also authorized to certify the signatures and set a firm date of a letter under the hand by enrolling in a special book (legalization). Besides qualify predetermined law in order for a certificate to be authentic, a Notary in his duties shall carry out their duties with discipline, professional and moral integrity should not be in doubt. What is stated in the beginning and end of the deed is the responsibility of the notary is a phrase that reflects the true situation at the time of a deed. As stated in Article 65 UUJN: